Faith, Inflammation, and Immunity: Investigating the Association Between NLR and Spiritual Coping in HIV-Positive Patients - Nurhayatun, Evi; Wijaya, Hanifan Danu; Ulfia, Mila (Institute of Topical Disease Universitas Airlangga, 2026)
Chronic HIV infection not only compromises immune function but also induces psychological comorbidities, particularly anxiety. Elevated anxiety levels contribute to increased systemic inflammation, often reflected by a higher Neutrophil-to-Lymphocyte Ratio (NLR) and decreased quality of life (QoL). Self-Surrender Practice (SSP), which integrates respiration regulation and religious meditation, has demonstrated potential for the reduction of psychological stress and its biological correlates. This study investigates the effect of Self Surrender Practice (SSP), a religiously rooted relaxation technique, on Neutrophil-to-Lymphocyte Ratio (NLR) and Quality of Life (QoL) among HIV patients with anxiety. This study used a pre-test-post-test randomized controlled trial design with a control group. Based on their Hamilton Anxiety Rating Scale scores, forty patients with HIV and anxiety disorders were divided into two equal groups: control and intervention. A full blood count test was used to determine NLR, and the WHOQOL-BREF questionnaire was used to assess QoL. Data were examined using paired and independent t-tests, with a significance level of p < 0.05. This study was conducted at Dr. Moewardi Hospital, Surakarta, in January 2024. The results showed that study participants had comparable demographic and clinical characteristics between groups. Following the intervention, the SSP group showed a statistically significant decrease in mean NLR levels (p < 0.001) and improvement in QoL scores in the intervention group. These results suggest that higher NLR in HIV patients is associated with psychological distress and the severity of the disease, both of which can be improved by psychoreligious interventions.